The Complexity of Mathematics Teachers' Collaborative Professional Learning - McKie, Kelly (Université d'Ottawa / University of Ottawa, 2023)
This qualitative doctoral dissertation investigates the influence of the characteristics and conditions of complex learning systems on the emergence, sustainability, and diffusion of learning of four professional learning communities (PLCs). These PLCs were associated with a large-scale initiative focused on enhancing mathematics teaching and learning in Grade 9 in Ontario, Canada. This study took place in 2021, five years after completion of the professional learning initiative in 2016 and focused on deepening understanding of how learning emerged during the initiative and how learning was sustained and diffused after the original initiative. The study employed a complexity science informed multiple-case study approach, utilizing a variety of data collection methods including secondary analysis of original project data, surveys, and interviews. Data analysis followed an iterative process, using complexity science as a framework, to analyze data and identify key themes. Findings revealed that all the characteristics and conditions of complex learning systems manifested across the cases and the whole initiative. Key conditions and characteristics such as decentralized control, self-organization, and nestedness supported neighbour interactions which contributed to teacher learning. The Diffusion of Innovation model was utilized to better describe how and why these themes supported teacher learning. These findings contribute to the understanding of how to support teacher learning in educational contexts and provide insights for educators and researchers seeking to promote effective professional learning initiatives. In conclusion, this study highlights the need to consider educational settings as interconnected nested systems that interact to influence learning across different systems. Professional learning initiatives within these systems need to incorporate teacher agency over an extended time period to allow for the development of professional relationships and communities of learners. These communities were observed to self-organize in ways that best supported and sustained their own learning and allowed the learning to diffuse to others in learning systems. These findings underscore the importance of creating supportive environments that fosters collaboration, connections, teacher agency, and shared purpose, thereby enhancing professional learning and educational outcomes.
Keywords: Mathematics; Education; Teacher; Collaborative; Learning